PENERAPAN MANAJEMEN HIDUP SEHAT DALAM MENGATASI PENYEBARAN VIRUS COVID-19 DI DESA PADASUKA KECAMATAN BAROS KABUPATEN SERANG - Khaeruman; Adien Nurdiansyah; Iis Suryanah; Suflani; Ahmad Suherman; Fahad; Raden Irna Afriani (Bajang Institute, 2021)
Activities carried out in this Community Service are through socialization activities on the application of healthy life management in overcoming the spread of the Covid-19 virus pandemic in the form of counseling on healthy life management management for residents of Padasuka Village, Serang Regency. Solutions to mobilize healthy living management habits with a healthy life management socialization system in order to overcome the spread of the Covid-19 virus, as well as the need for masks and hand sanitizers in order to ensure health and break the chain of the spread of Covid-19. The objectives of this service activity are 1) Increase understanding of the application of healthy living management in overcoming the spread of the Covid-19 Virus; 2) implementing healthy living management habits in overcoming the spread of the Covid-19 Virus. In the midst of conditions that will spread the Covid-19 virus, it is very necessary to socialize the application of healthy life management and prevention efforts which bring benefits 1) increasing understanding of the dangers of the Covid-19 virus, 2) increasing knowledge about how to prevent being infected with the Covid-19 virus , 3) increasing knowledge of how to wash hands properly, 4) increasing knowledge of how to maintain body resistance with healthy life management, 5) knowing how to take steps to implement a healthy lifestyle.